Composition and cross-sectional area of muscle fibre types in relation to daily gain and lean and fat content of carcass in Landrace and Yorkshire pigs - Ruusunen, Marita; Sevón-Aimonen, Marja-Liisa; Puolanne, Eero (Agricultural Research Centre of Finland, 1996)
Tutkimuksessa verrattiin maatiais- ja yorkshire-sikarotuja keskenään määrittämällä histokemiallisesti longissimus- lihaksen lihassolutyyppien ominaisuuksia. Lisäksi selvitettiin histokemiallisten ominaisuuksien suhdetta eläimen kasvuun ja ruhon laatuun. Käsiteltävinä muuttujina olivat ikä, päiväkasvu, elopaino, teuraspaino, pH 1 - ja pH 2 -arvot, ulkofileen poikkipinta- ala sekä ruhon liha- ja rasvaprosentit. Lihassolut määritettiin myosiini ATPaasimenetelmällä ja luokiteltiin kolmeen ryhmään: I, IIA ja IIB. Lihassolujen lukumäärä laskettiin jakamalla fileen poikkipinta-ala keskimääräisellä lihassolun poikkipinta-alalla. Maatiaisen longissimus-lihaksessa oli tyypin I lihassolujen poikkipinta-ala pienempi ja tyypin IIB lihassolujen poikkipinta-ala suurempi kuin yorkshiren longissimus-lihaksessa. Leikkojen longissimus-lihaksessa tyypin IIB lihassolut olivat suurempia kuin imisien longissimus-lihaksessa. Rotu ja sukupuoli eivät vaikuttaneet ulkofileen lihassolujen määriin. Maatiaisessa pH 1 -arvot olivat alhaisempia kuin yorkshiressa. Imisissä oli ruhon lihamäärä suurempi ja rasvamäärä pienempi kuin leikoissa. Myös ulkofileen poikkipinta-ala oli imisissä suurempi kuin leikoissa. Eri eläinyksilöiden histokemialliset, kasvu ja ruhon laatuominaisuudet vaihtelivat paljon. Histokemialliset ominaisuudet eivät vaikuttaneet eläimen kasvuun ja ruhon laatuominaisuuksiin.

The muscle fibre-type properties of longissimus were compared between Landrace and Yorkshire breeds and between the sexes in an attempt to shed light on the relationship of these histochemical parameters to animal growth and carcass composition. Muscle fibres were classified into three groups, type I, type IIA and type IIB, using the myosin ATPase method. At a given live weight, the cross-sectional area of type I fibres (CSA I ) was smaller (p<0.01) and the cross-sectional area of type IIB fibres (CSA IIB ) larger (p<0.01) in longissimus of Landrace than in that of Yorkshire. The CSA IIB (p<0.01) was larger in gilts than in castrated males. At an average live weight of 97 kg, the Landrace pigs were significantly younger (p<0.01) than the Yorkshire pigs. The pH 1 value of Landrace was lower (p<0.01) than that of Yorkshire. The percentage of high-value cuts in carcass with head (M%) was lower (p<0.01) and the percentage of fat in back and loin (F%) higher (p<0.01) in castrated males than in gilts. The cross-sectional area of loin (CSA loin ) was larger (p<0.01) in gilts than in castrated males. All the histochemical and other traits varied considerably between the animals. The correlations between histochemical properties and growth and histochemical properties and carcass composition were rather low.
Keywords: Ko; sika; sikarodut; lihakset; pig breed; muscle fibre cross sectional area; longissimus; daily gain; carcass traits